2021
DOI: 10.1371/journal.pone.0254949
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing walking trips. Evidence from Gdynia, Poland

Abstract: Political support for active mobility is growing for many reasons, including land use planning, health, and improved mobility. As the vital part of many cities is their central area, decision-makers need to know what factors are essential for increasing walkability. This paper aims to identify the main factors affecting the walkability of the city centre of Gdynia (Poland). To achieve this, the research design was adjusted to the specificity of the local use case. Based on primary data collected via personal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 91 publications
(96 reference statements)
0
9
0
Order By: Relevance
“…The first step to determining the area coverage in the public minivan stop was analyzing the factors swaying it. According to Wolek et al (2021), factors that influence someone's walkability differ in each location based on its area condition and surrounding environment. Therefore, there were 35% of respondents from public society through an open-question survey.…”
Section: Findings and Discussion A Factors Affecting Walkabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The first step to determining the area coverage in the public minivan stop was analyzing the factors swaying it. According to Wolek et al (2021), factors that influence someone's walkability differ in each location based on its area condition and surrounding environment. Therefore, there were 35% of respondents from public society through an open-question survey.…”
Section: Findings and Discussion A Factors Affecting Walkabilitymentioning
confidence: 99%
“…The social condition affects one's willingness to walk to transportation services (Sukor & Fisal, 2018) (Wolek et al, 2021) and vehicle ownership (Mulley et al, 2017). People with low economic levels will use 'cheap' transportation modes.…”
Section: Social Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to World Tourism Organization, in 2020, a sharp decline in global entertainment revenues against the backdrop of a global recession was recorded -5.6% or 120 billion USD (United States dollar) compared to those recorded in 2019. The indicators with the data recorded in 2008, when another global economic crisis occurred, showed that the costs of the population associated with the purchase of entertainment goods and services decreased by only 3%; therefore, it can be concluded that the impact of the pandemic caused much more damage to the entertainment industry, 1.5 times stronger than the crisis of 2008 (Chandler and Cuneo, 2021;Comunian, and England, 2020;Wolek et al, 2021).…”
Section: Introductionmentioning
confidence: 91%
“…Mountain trails and hiking are often the focus of current research, which in various ways creates the knowledge needed to better understand their characteristics and effects. Studies of the motives for hiking (or other trail activities) or selecting particular trails or landscapes (Snyder et al, 2008;Mohd Taher et al, 2015;Collins-Kreiner & Kliot, 2016;Li et al, 2017;Tomik et al, 2017;Upadhayaya, 2018;Korpilo et al, 2018;Sales et al, 2018;Wolek et al, 2021) contribute to understanding important aspects of hiker safety or satisfaction, or focus on collecting hikers' opinions to support management of the trails and risk prevention (Slabbert and Du Preez, 2017a;2017b). Further studies assess hikers' experiences or satisfaction at the beginning, during, or after the activity (Gauvin et al, 2005;Deng et al, 2013;Mohd Taher et al, 2015;Apollo, 2017;Li et al, 2017;Korpilo et al, 2018;Peterson et al, 2018;Arts et al, 2021;Daniel et al, 2021;Sukumar & Ahmed, 2021;Wang et al, 2022), some of them emphasise the temporal aspect of hiking (Pitman et al, 2012;Magyari-Saska & Dombay, 2012).…”
Section: Mountain Trails and Hiking In Research: The Contextmentioning
confidence: 99%